Analisis Peran Teknologi Informasi Pada Pembelajaran Sekolah Madrasah Aliyah Swasta - Henny Puspitasari; Nurbani (STAI AL-AMIN, 2026)
Information Technology is the result of human engineering on the process of delivering information from the sender to the recipient so that the delivery of the information will be faster, more widely distributed, and longer stored. That there are problems regarding the use of Information technology in learning, there are teachers who have not mastered and utilized technology in learning optimally. Then for facilities such as computers there are some that can no longer be used because they are damaged. The purpose of this study is to find out: 1. The role of information technology in learning at SMAS Hidayatul Muhsinin; 2. The use of information technology at SMAS Hidayatul Muhsinin. The research method used is a descriptive qualitative method. Data collection techniques are carried out through observation, interviews, and documentation. The research subjects are teachers. The results of the study show that the use of Information Technology at SMAS Hidayatul Muhsinin has utilized information technology in learning quite well, this is because the information technology used such as laptops, infocus, cellphones and speakers can facilitate teachers in the learning process. Meanwhile, the conclusion of this study is that the role of information technology at SMAS Hidayatul Muhsinin is very important because it can help teachers to facilitate the learning process, for example, teachers use laptops, projectors, and cellphones in the learning process to help the learning process become better. However, facilities related to information technology at this school are still lacking and the use of information technology at SMAS Hidayatul Muhsinin is quite good because teachers use information technology tools in learning.